Roles of IL-35-producing T and B cells in anti-acetylcholine receptor antibody-positive myasthenia gravis. (January 2022) - Li, Li-Min; Zhang, Lin-Jie; Zhu, Si-yu; Liu, Xiao-jiao; Yi, Ming; Qi, Yuan; Wang, Jing; Zhang, Da-Qi; Yang, Li
Highlights: The potential roles of IL-35-producing T and B cells and serum IL-35 levels in the pathogenesis of MGremain unclear. The percentages of IL-35-producing CD4 + CD25 + T cells and CD19 + B cells were significantly lower in patients with AChR-MG than in HCs. Further, the proportions of IL-35-producing T cells and B cells and serum levels of IL-35 increased after treatment. IL-35 may represent a potential biomarker for the clinical evaluation of MG. Abstract: Background: Interleukin 35 (IL-35) plays an anti-inflammatory in numerous autoimmune diseases. However, the potential roles of IL-35-producing T and B cells and serum IL-35 levels in the pathogenesis of myasthenia gravis (MG) and its association with disease activity in patients with MG remain unclear. Methods: The percentages of IL-35-producing CD4 + CD25 + T cells and CD19 + B cells among peripheral blood mononuclear cells were determined in 37 patients with anti-acetylcholine receptor (AChR) antibody-positive MG and 35 healthy controls (HCs) by performing a flow cytometry analysis. Serum IL-35 levels in participants were determined using an enzyme-linked immunosorbent assay. Further, the correlations between IL35 levels and disease activity were analysed. Results: The percentages of IL-35-producing CD4 + CD25 + T cells and CD19 + B cells were significantly lower in patients with anti-AChR antibody-positive MG than in HCs (p = 0.001 and p = 0.002, respectively). Furthermore, patients with thymoma and patients with generalized MG had lower percentages of IL-35-producing CD4 + CD25 + T cells and CD19 + B cells than those without thymoma and those with ocular MG (p = 0.001 and p = 0.003; p = 0.008 and p = 0.001, respectively). Interestingly, the suppression of IL-35 secretion correlated negatively with the activities of daily living scores of patients with MG (r = -0.4774, p = 0.0028) and the quantitative MG scores (r = -0.4656, p = 0.0037). The proportions of IL-35-producing T cells and B cells and serum levels of IL-35 increased after treatment. Conclusions: IL-35 may represent a potential biomarker for the clinical evaluation of MG.